Organized blood clot masquerading as endobronchial tumor: A review of management and recent advances. (2018) - Saladi, Lakshmi; Lvovsky, Dmitry
Abstract: Central airway obstruction, a frequently encountered emergency, is usually associated with blood clots, tumors, foreign bodies or mucus plugs. Airway obstruction due to blood clots can be seen as a complication of lung malignancies, infections, bronchiectasis, arteriovenous malformations or pulmonary infarction. In patients with long standing blood clots, the thrombus gets organized and firmly adherent to the airway. The diagnosis is often misleading as these clots mimic tumors clinically and on imaging. Hemoptysis is the most common presenting symptom though many patients can be asymptomatic. Direct visualization with bronchoscopy is required to establish a diagnosis. Life-threatening respiratory impairment is an indication for emergent clot retrieval. Management of these blood clots, especially when organized, is challenging. Initial attempts at removal should include suctioning, lavage or forceps extraction. When unsuccessful, further management options include balloon catheter dislodgement, use of topical thrombolytics, rigid bronchoscopy and cryoextraction.